ANALISIS MODAL BANK SAMPAH INDUK KOTA PALEMBANG DALAM PERSPEKTIF EKONOMI SYARIAH - Andiwijaya, Andiwijaya; Anwar, Saiful; Setiadi, Iwan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Sustainable waste management has become increasingly important in major cities, including Palembang, amid the rising volume of waste generated daily. Waste banks play a crucial role in this effort; however, limited financial, social, and intellectual capital remain challenges that need to be addressed to improve their operational effectiveness and capacity. This study aims to analyze the capital of the central waste bank in Palembang. The research employed a qualitative case study approach, with the researcher acting as the main instrument and data sources selected purposively and through snowball sampling. Data was collected using triangulation techniques, and the analysis was inductive/qualitative, emphasizing meaning over generalization. The findings indicate that most waste banks in Palembang rely on limited financial capital, which impacts their operational capacity and business development. A strong social capital has formed among waste bank managers, communities, and other related parties, but it requires further strengthening to expand networks and support. As for database capital, the level of knowledge and skills among waste bank managers in managing waste with a focus on customer databases, waste volumes, types of waste, and product packaging databases also needs improvement. Based on these findings, it is recommended that waste banks in Palembang improve access to financial resources, such as partnerships with financial institutions or government funding, to expand their operational capacity and business development. Additionally, strengthening social capital should continue through collaboration with communities and related parties to expand networks and support. Finally, waste banks should enhance their database capital by strengthening data infrastructure to enable optimal data recording, analysis, and utilization. This will improve waste management effectiveness, inspire recycled product innovation, and create collaboration opportunities with companies and related institutions, such as partnerships for Corporate Social Responsibility (CSR) programs.